1994
DOI: 10.1111/j.1365-2710.1994.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Opiate antagonists for the treatment of schizophrenia

Abstract: SUMMARYbrospinal fluid (CSF) of unmedicated schizophrenic Numerous studies suggest that opiate antagonists may have antipsychotic properties. A review of the literature describing the use of naloxone to treat schizophrenic patients has shown mixed results. The three studies on naltrexone have found no benefit in controlling auditory hallucinations. We present a synopsis of these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Similarly, our novel, preliminary data on increased 3  H]DAMGO binding in BP are intriguing and deserve further investigations. Both findings add to the long held argument that the opioid system plays an important role in the pathophysiology and/or outcomes of psychiatric disorders [51]. …”
Section: Discussionsupporting
confidence: 56%
“…Similarly, our novel, preliminary data on increased 3  H]DAMGO binding in BP are intriguing and deserve further investigations. Both findings add to the long held argument that the opioid system plays an important role in the pathophysiology and/or outcomes of psychiatric disorders [51]. …”
Section: Discussionsupporting
confidence: 56%
“…On the basis of the hypothesis that opioidergic mechanisms are involved in the pathophysiology and symptoms of schizophrenia (Volavka et al, 1979;Schmauss and Emrich, 1985;Nemeroff and Bissette, 1988), opioid antagonists were evaluated for potential antipsychotic efficacy in numerous clinical trials (McNicholas and Martin, 1984;Nemeroff and Bissette, 1988;Welch and Thompson, 1994). On the whole, they were safe and well tolerated and resulted in significant improvements of various aspects of schizophrenic symtomatology such as positive and deficit symptoms, polydipsia, alcoholism, and tardive dyskinesia in some (Watson et al, 1978;Lehmann et al, 1979;Berger et al, 1981;Nishikawa et al, 1994a, b;Marchesi et al, 1995;Petrakis et al, 2004;Wonodi et al, 2004), but not all (Volavka et al, 1977;Pickar et al, 1982) participants.…”
Section: Opioid Antagonists May Improve Hedonic Deficits In Patients mentioning
confidence: 99%
“…In addition, opioid μ receptors modulate mesolimbic-mesocortical dopamine activity [ 7 ]. It has been suggested that some symptoms might be precipitated by alterations in BE level associated with a dysfunction in the modulatory effect of endogenous opioids on the dopaminergic system [ 8 ].…”
Section: Introductionmentioning
confidence: 99%